b) \(x^2-4y^2-2x+4y\)
\(=\left(x^2-4y^2\right)-\left(2x-4y\right)\)
\(=\left[x^2-\left(2y\right)^2\right]-\left(2x-4y\right)\)
\(=\left(x-2y\right).\left(x+2y\right)-2.\left(x-2y\right)\)
\(=\left(x-2y\right).\left(x+2y-2\right)\)
c) \(x^3-25x\)
\(=x.\left(x^2-25\right)\)
\(=x.\left(x^2-5^2\right)\)
\(=x.\left(x-5\right).\left(x+5\right)\)
d) \(x^4+64\)
\(=\left(x^2\right)^2+16x^2+64-16x^2\)
\(=\left[\left(x^2\right)^2+16x^2+64\right]-16x^2\)
\(=\left[\left(x^2\right)^2+2.x^2.8+8^2\right]-16x^2\)
\(=\left(x^2+8\right)^2-16x^2\)
\(=\left(x^2+8\right)^2-\left(4x\right)^2\)
\(=\left(x^2+8-4x\right).\left(x^2+8+4x\right)\)
g) \(3x^2-8x+5\)
\(=3x^2-5x-3x+5\)
\(=\left(3x^2-3x\right)-\left(5x-5\right)\)
\(=3x.\left(x-1\right)-5.\left(x-1\right)\)
\(=\left(x-1\right).\left(3x-5\right)\)
Chúc bạn học tốt!